Progranulin Is Associated with Disease Activity in Patients with Rheumatoid Arthritis - Lucie Andrés Cerezo; Markéta Kuklová; Hana Hulejová; Zdeňka Vernerová; Nikola Kaspříková; David Veigl; Karel Pavelka; Jiří Vencovský; Ladislav Šenolt (Mediators of Inflammation)
Objective. Progranulin (PGRN) is implicated in the pathogenesis of rheumatoid arthritis (RA). The aim of this study was to assess the relationship between PGRN and disease activity in RA. Methods. PGRN levels were evaluated in patients with RA (n=47) and OA (n=42) and healthy controls (n=41). Immunohistochemical analysis of PGRN in synovial tissues was performed. The association between PGRN and C-reactive protein (CRP), disease activity score (DAS28-CRP), and health assessment questionnaire (HAQ) was studied. Results. Circulating PGRN was elevated in patients with RA and OA compared to healthy controls (227.1±100.2 and 221.5±102.5 versus 128.1±34.7 ng/mL; P<0.001). Synovial fluid levels of PGRN were higher in patients with RA compared to OA (384.5±275.3 versus 241.4±165.2 ng/mL; P=0.002). PGRN expression was significantly upregulated in the synovial tissue of RA patients particularly in the inflammatory infiltrates. Serum PGRN levels correlated with DAS28 (r=0.327, P=0.049) and HAQ score (r=0.323, P=0.032), while synovial fluid PGRN correlated only with HAQ (r=0.310, P=0.043) in patients with RA. PGRN levels were not associated with CRP or autoantibodies. Conclusions. This study demonstrates increased PGRN expression at local sites of inflammation and association between PGRN levels, disease activity, and functional impairment in patients with RA.